SPECIFICITY OF LEARNING RUSSIAN AS A FOREIGN LANGUAGE - Djalmatova, Zamira (АКТУАЛЬНОЕ В ФИЛОЛОГИИ, 2021)
his article examines the problems of learning Russian as a foreign language.The characteristic features of the meaning of the Russian language are analyzed. The effectiveness of studying the Russian language and the